2013
DOI: 10.1016/j.regsciurbeco.2012.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Agglomeration premium and trading activity of firms

Abstract: Firms may benefit from proximity to each other due to the existence of several externalities. The productivity premia of firms located in agglomerated regions an be attributed to savings and gains from external economies. However, the capacity to absorb information may depend on activities of the firm, such as involvement in international trade. Importers, exporters and two-way traders are likely to employ a different bundle of resources and be organised differently so that they would appreciate inputs and inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
7

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 57 publications
(53 reference statements)
0
9
0
7
Order By: Relevance
“…We found that the agglomeration effects of the Japanese community are strongly distance-bound, experiencing significant diminishing returns after about 15 km from the origin of agglomeration (Békés & Harasztosi, 2013). We explored the ranges between the upper and lower boundaries around 15 km, with two criteria from our theory in mind.…”
Section: Defining Core and Periphery With Geo-visualizationmentioning
confidence: 99%
“…We found that the agglomeration effects of the Japanese community are strongly distance-bound, experiencing significant diminishing returns after about 15 km from the origin of agglomeration (Békés & Harasztosi, 2013). We explored the ranges between the upper and lower boundaries around 15 km, with two criteria from our theory in mind.…”
Section: Defining Core and Periphery With Geo-visualizationmentioning
confidence: 99%
“…Оценки производитель-ности труда показали существенное преимущество города по сравнению со средними характеристиками для стран ОЭСР (Ahrend, Farchy, Kaplanis, Lembcke, 2017), Японии , Италии (Cainelli, Fracasso, Marzetti, 2015), Западной Европы (Ciccone, 1996;Ciccone, 2002;, Восточной Европы (Békés, Harasztosi, 2013;Bruhart, Mathys, 2008) и России (Гордеев, Магомедов, Михайлова, 2017; Изотов, 2017; Коло-мак, 2011; Коломак, 2015; Русановский, Марков, 2015). Анализ предприятий Швейцарии выявил географические факторы риска банкротства, большую устойчивость демонстрируют фирмы, расположенные в центре городских агломераций (Buehler, Kaiser, Jaeger, 2012).…”
Section: источники и механизмы агломерационной экономики городаunclassified
“…A hazai és a külföldi tulajdonú vállalatok közötti különbségeket jól mutatja, hogy a külföldi, termelékenyebb vállalatokból hazai cégekbe áramló munkaerő jelentősen javítja a magyar cégek termelékenységét (Csáfordi, Lőrincz, Lengyel, Kiss 2016). Továbbá, a nemzetközi kereskedelembe sikerrel bekapcsolódó cégeknek több előnye származik az agglomerációs előnyökből, mint a nemzetközi kereskedelmi kapcsolatokkal nem rendelkező vállalatoknak (Békés, Harasztosi 2013).…”
Section: Elméleti Háttér éS a Kutatás Kontextusaunclassified
“…Egyrészt a feldolgozóiparban a vállalati adatok nagyobb valószínűséggel esnek egybe a tényleges gazdasági tevékenység helyszínével. E vállalatok 90%-a egyetlen telephellyel rendelkezik, a fennmaradó esetekben pedig az alkalmazottak kétharmada a vállalat székhelyén dolgozik (Békés, Harasztosi 2013). Másrészt a kapcsolódó változatosságból származó előnyök nagyobb valószínűséggel érvényesülnek a feldolgozóiparban (Basile, Pittiglio, Reganati 2017; Bishop, Gripaios 2010).…”
Section: Az Empirikus Kutatásunclassified